Early Detection of Microplastic Contamination in Fishes In The Sukamade Shoreline, Meru Betiri National Park - Ariyunita, Selvi; Subchan, Wachju; Fitria, Anisa (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Microplastics (< 5 mm) have the potential to be a threat to organisms. However, the study of microplastic contamination in conservation areas, especially in Indonesia, is still limited. The Sukamade is a conservation area that is potentially contaminated by microplastic. This study aims to detect microplastic contamination in fish caught in the Sukamade shoreline as an early warning of the potential threat to biodiversity. The study was conducted from September to December 2022. The methods used include: 1). Fish sampling, 2). Dissection and removal of the gills and gastrointestinal tract; 3). Microplastic characterization based on sizes, shapes, and colors; 4). Data analysis. This is the first report that 451 microplastic particles were detected in four fish caught from the Sukamade shoreline: two individuals of Senangin fish (Eleutheronema sp.), one individual of Lemuru fish (Sardinella sp.), and one individual of Lowang totol fish (Trachinotus sp.). The presence of microplastic in the gastrointestinal tract of fishes shows the possibility of microplastic translocation in tissue and another tropic level, causing health problems in organisms and the community as a constituent of biodiversity.